New perspectives on morphological and genetic variability of Corynosoma bullosum [Linstow, 1892] parasitizing southern elephant seals from the Antarctic Peninsula - Soto, Florencia Anabella; Rodríguez, S.M.; Leonardi, María Soledad; Negrete, Javier; Cremonte, Florencia (Journal of Helminthology)
Previous descriptions of Corynosoma bullosum (Linstow, 1892) show that specimens vary greatly in the proportions of different body structures, measurements of females and males, number of rows of hooks, and egg measurements, among other features. We redescribe this species from specimens found in southern elephant seal faeces from King George Island. We also provide a molecular characterization, in addition to 5.8S and internal transcribed spacer (ITS) existing sequences. We examined 41 elephant seals, and 30 adult acanthocephalans were found in 15 of them. The specimens were identified as belonging to the genus Corynosoma due to each having a tubular body with an inflated anterior part forming a thorny disk and the posterior part bearing somatic spines on the ventral surface, and genital spines surrounding the genital pore. Individual morphology corresponded to C. bullosum: large size, marked sexual dimorphism, and proboscis with 16-18 rows of spines with 11-15 spines per row. The molecular profile of three specimens of C. bullosum was analysed using 18S rDNA. We inferred phylogenetic relationships of the family Polymorphidae using maximum likelihood and Bayesian inference. We provide an updated morphological redescription for C. bullosum including electron microscopy photographs and molecular data. The 18S gene sequences showed low genetic variation and supported that C. bullosum is a sister to Corynosoma australe. Fil: Soto, Florencia Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Rodríguez, S.M. Universidad Bernardo O'higgins; Chile. Universidad Católica de la Santísima Concepción; Chile Fil: Leonardi, María Soledad. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Negrete, Javier. Consejo Nacional de ...